BANK LIQUIDITY AND PROFITABILITY IN THE POLISH BANKING SECTOR - Pavla Klepkova Vodova (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
Liquidity and profitability are two very important aspects of the banking business. The aim of this paper is to thoroughly evaluate the development of bank profitability and liquidity in the Polish banking sector and to analyze the link between profitability and liquidity ratios with the use of correlation analysis over the period 2007-2013. Liquidity of the Polish banking sector has decreased during this period. Small banks are the less liquid, the most dependent on other sources of funding and their net interbank position is the most vulnerable. Profitability of Polish banks could be higher. With the exception of interest margin, profitability increases with size of the bank. The values of the Pearson´s correlation coefficient showed mixed results: the links between profitability and liquidity ratios differ among individual groups of banks.